The sugar contents of commercial samples of tobacco leaves - Ram, Jaghat B.; Salcedo, Ignacio S. (Quezon City Department of Chemistry, College of Liberal Arts, University of the Philippines Diliman, 1959)
The reducing sugars of the tobacco samples have been determined by the Munson-Walker method. The principle involved in this determination is based in the property of reducing sugar to reduce alkaline tartrate solution of copper sulfate to Cu2O. the weight of the reducing sugar is calculated from Munson-Walker table.
The preliminary treatments for the reducing sugar analysis involved drying of samples at 50°C for at least 24 hours, grinding to 100 mesh, and solvent extraction of the sugar content. For convenience, the standard method of sugar extraction employing 80% alcohol is modified to water extraction; the sugar content is extracted by boiling water.
The reducing sugar content of 15 samples of tobacco varied from 0.18 to 11.13 percent. Dark colored samples (dark brown) contained small amounts of reducing sugars; higher percentage are found in the light-colored ones (light brown to yellow).
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, March 1959.
Keywords: Tobacco; Sugar